Functional Character of the Performance Management - Gergely, Éva (International Journal of Engineering and Management Sciences, 2016)
Performance management is a complex system, researching its modifying factors and elements, using the research results may significantly improve the success of the operation of organizations. Performance management functions are the followings: planning performance, developing measuring tools, communicating expectations, monitoring and quantifying performance, performance appraisal, feedback on performance, communicating personnel decisions, developments based on results. Along these task groups researches may be carried out separately or by aggregating several of them, in this way certain sub-fields of  performance management may be investigated in a more detailed way. In my research the characteristics of performance management systems operating in profit-oriented organizations were examined from the aspect of the management.